THE EFFECT OF AQUEOUS-METHANOL CRUDE EXTRACT AND ACTIVE FRACTION FROM Gracilaria corticata AGAINST CYTOTOXIC ACTIVITY AND CYTOCHROME C RELEASE FROM MITOCHONDRIA IN HUMAN BREAST CANCER CELL LINE (MCF-7) - FAUZIA PURNAMA (NIM : 20515013), FARIZA
Indonesia is one of the greatest producer for seaweed (macroalgaes) in the world. Seaweed is one of resources of natural bioactive compounds such as lipids, polysaccharides, proteins, phenolic compounds, flavonoids, and terpenoids. The bioactive compounds can be used for health and pharmacy. Gracilaria sp. has been known abundantly in Indonesia and its bioactive compounds has a potential to be developed as anti-cancer drug. Breast cancer is one of the most leading cause of cancer death in women worldwide. Nowadays treatment for cancer through chemotherapy and radiotherapy induce side effect such as cardio-toxicity and cancer cells resistance to the drugs. Treatment through natural product could deliver minimal side effect and mostly safe. One of the characteristic from cancer is its ability to avoid programmed cell death (apoptosis). The intrinsic pathway of apoptosis (mitochondria) is often studied to observe the effects of a compound or drug which could be used as a chemotherapy agent. This pathway is characterized by alteration in permeability of the mitochondrial membrane when it receives apoptotic stimulus such as toxic compounds, radiation and oxidative stress. Alteration in mitochondrial membrane permeability generate the formation of pores on outer membrane of mitochondria which furthermore cause releasing of cytochrome c from inter-membrane space of mitochondria. The objective of this research was to discover the effect of aqueous-methanol crude extract of Gracilaria corticata and active fractions against to cytotoxic activity and cytochrome c release from mitochondria in human breast cancer cell line (MCF-7). In this study, cytotoxic activity of the crude extract and its fractions was examined through MTT assay and concentration of cytochrome c released from mitochondira in treated cells was determined by using UV-Vis spectrophotometry. Aqueous-methanol crude extract from Gracilaria corticata was obtained by maceration using methanol: chloroform: phosphate buffer 50 mM pH 7.6 (2:1:0.5 v/v). The result revealed that crude extract was 1.13 % (w/w) with content of water was 88.9 % (w/w for wet sample). Crude extract separated in 7 major fractions by column chromatography and grouped based on similar UV-Vis spectra were collected from 200 to 420 nm, which include wavelength of for phenolic and flavonoid compounds. Based on TPC (Total Phenolic Content) and TFC (Total Flavonoid Content) assay, FG2, FG6, FG7 were the highest value of phenolic content (61.36 Ã‚Â± 4.37; 56.03 Ã‚Â± 1.94; and 77.14 Ã‚Â± 3.36 mg GAE/g fraction) and flavonoid content (54.04 Ã‚Â± 6.68; 47.64 Ã‚Â± 1.55; and 65.65 Ã‚Â± 3.83 mg QE/g fraction) among other fractions, therefore it was used further for cytotoxic activity test against MCF-7 cell line. MTT data showed that IC50 (Inhibitor Concentration 50) FG7 (20.29 μg/mL) has lower value compared to crude extract of aqueous-methanol Gracilaria Corticata (33.01 μg/mL), FG2 (33.47 μg/mL), and FG6 (50.75 μg/mL). According to National Cancer Institute, The IC50 of FG7 has cytotoxic activity whereas crude extract, FG2 and FG6 were less cytotoxic. Study on the releasing of cytochrome c showed that doxorubicin (1 μg/mL) was able to induce cytochrome c released from mitochondria about 21.46 μM. Treatment with IC50 of aqueous-methanol crude extract from Gracilaria corticata (33.01 μg/mL) toward MCF-7 cell could induce cytochrome c released from mitochondria about 1.47 μM or equal to 6.87% of doxorubicin, while treatment with IC50 FG7 (20.29 μg/mL) can induce cytochrome c released about 8.82 μM or equal to 41.07 % of doxorubicin. Further analysis of UV light spectrum revealed that FG7 with wavelength peak of 211, 261, 263, 265 and 338 nm was estimated as a mixture of phenolic, flavonoid and glycoside. It could be concluded that cytotoxic compound in FG7 containing phenolic, flavonoid and glycoside compounds have high cytotoxic activity that caused cytochrome c release more effective than aqueous-methanol crude extract from Gracilaria corticata.